PENGUJIAN PECKING ORDER THEORY (POT): Pengaruh Leverage Terhadap Pendanaan Surplus dan Defisit pada Industri Manufaktur di Bursa Efek Indonesia - Ari Christianti (UKDW, 2008)
This research is empirically examines the Pecking Order Theory (POT). This is important since the POT discuss the factors effected the level of debt used by the company such as: the capacity of deficit due to internal cash flow inadequacy for exercising the investment and its commitment to regularly pay deviden. On doing so, this research is intended to specifically examnie the effect of surplus and deficit financing on the use of debt. The samples are drawn from companies witin manufacturing sector which are listed at the Indonesian Capital Stock Exchange during 2000-2005. Furthermore the data will be analyzed using the regression with dummy variables. The result shows, there is a negatively effect between long term debt with deficit. The possible explanation is market and economic condition effect the capital structure decision.